2016
DOI: 10.4155/fmc.15.191
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Identification of Neuroprotective Agents: G-Scale Synthesis, Pharmacokinetic Evaluation and Cns Distribution of ( R )-Rc-33, a Promising Sigma1 Receptor Agonist

Abstract: (R)-RC-33 may be a promising candidate for in vivo studies in animal models of neurodegenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 15 publications
4
28
0
Order By: Relevance
“…[14,[17][18][19] High-affinity s 1 Rl igandsh ave been considered to play an important role in the treatment of various neurodegenerative disorders, including Parkinson's, Alzheimer's, and Huntington's diseases,d ementias, cognitive aging, depression, schizophrenia, neuropathicp ain, drug addiction, stroke, HIV infection, and cancer. [20][21][22][23][24][25][26][27][28][29] Unlike s 1 Rs, s 2 Rs are less understood and have not yet been cloned. Recently,t he progesterone receptor membrane component 1( PGRMC1) has been proposeda st he s 2 R binding site, [30] although this wasq uestioned by other evidence supporting that the two targets are two different proteins.…”
Section: Introductionmentioning
confidence: 99%
“…[14,[17][18][19] High-affinity s 1 Rl igandsh ave been considered to play an important role in the treatment of various neurodegenerative disorders, including Parkinson's, Alzheimer's, and Huntington's diseases,d ementias, cognitive aging, depression, schizophrenia, neuropathicp ain, drug addiction, stroke, HIV infection, and cancer. [20][21][22][23][24][25][26][27][28][29] Unlike s 1 Rs, s 2 Rs are less understood and have not yet been cloned. Recently,t he progesterone receptor membrane component 1( PGRMC1) has been proposeda st he s 2 R binding site, [30] although this wasq uestioned by other evidence supporting that the two targets are two different proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The new compounds series is characterized by a arylalkylaminoketone scaffold, which bears the structural elements of our developed S1R agonist RC-33, the well-known AChE inhibitor Donepezil and the antioxidant molecule Curcumin. Their affinity and selectivity towards S1R, their inhibition of AChE and their antioxidant profile were determined [1][2][3]. In the present communication we present the structure optimization of hit compounds, with the final aim to achieve viable tools for the treatment of neurodegenerative pathologies.…”
mentioning
confidence: 99%
“…Nevertheless, they are suitable only for systemic administration and fairly expensive, hence academic and industrial environments are still addressing their efforts towards the development of new drugs Chamberlain et al (2016). Considering that neurodegeneration is a contributory factor in the onset of MS, Sigma 1 Receptor (S1R) could play a crucial role in MS , Peviani et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…During the years, our interdisciplinary research group identified compound (R)-RC-33, as a new selective S1R agonist with an excellent S1R affinity (Ki= 1.8 nM) along with high selectivity over other receptors, including S2R, and good in vitro metabolic stability Rossi et al (2010), , Marra et al (2016). On the bases of these results, (R)-RC-33 has been selected as lead compound for MS preliminary biological assay.…”
mentioning
confidence: 99%
See 1 more Smart Citation